"Assessing exposure of printing factory workers in thailand to selected heavy metals using urine and hair as non-invasive matrices" - Patthrarawalai Sirinara; Yupin Patarapongsant; Siwaporn Nilyai; Kanidta Sooklert; Thasinas Dissayabutra; Rojrit Rojanathanes; Amornpun Sereemaspun (BMC, 2023)
Abstract Background There are few thorough studies on the extent and inter-element relationships of heavy metal contamination in printing factory workers, especially in developing countries. The objective of this study was to determine the levels of eight heavy metals, including arsenic (As), cadmium (Cd), chromium (Cr), nickel (Ni), cobalt (Co), lead (Pb), mercury (Hg), and manganese (Mn), in urine and scalp hair of printing industry workers, and assess inter-element correlations. Methods We examined a total of 85 urine samples and 85 scalp hair samples (3 cm hair segments taken from near the scalp) in 85 printing workers from a printing house in Bangkok, Thailand. We used an interviewer-administered questionnaire about participants' printing techniques, work characteristics, and work environment. Urine and scalp hair samples were analyzed for levels of each element using the inductively coupled plasma optical emission spectrometry (ICP-OES) technique. Results As, Cd, Cr, Ni, Pb were detected in urine with the geometric mean concentration range of 0.0028-0.0209 mg/L, and Hg, Pb, Ni, Cd, Co, Mn, Cr were detected in hair samples (0.4453-7.165 mg/kg dry weight) of printing workers. The geometric mean Ni level was significantly higher in the urine of production line workers than back-office personnel (0.0218 mg/L vs. 0.0132 mg/L; p = 0.0124). The other elements did not differ significantly between production line and back-office workers in either urine or hair. There was also a strong, statistically significant positive correlation between Ni and Co levels in hair samples of workers (r = 0.944, p < 0.0001). Conclusions Average concentrations of most of the metals in urine and hair of printing workers were found to be above the upper reference values. The significantly higher concentrations of Ni in production line workers might be due to more exposure to printed materials. A strong inter-element correlation between Ni and Co in hair samples can increase stronger health effects and should be further investigated. This study reveals possible dependencies and impact interactions of heavy metal exposure in printing factory workers.